Archival Practice and the Historiography of Education in South Africa: An Overview of Government Collections on Education (Yesterday & Today Journal for History Education in South Africa and abroad, 2025)
Archives provide a large part of the raw materials with which historians construct histories. How these repositories arrange this material, and what they consider as priorities for accessioning it, have a profound influence on what material is more within reach for historians. An investigation into the records available at the National Archives and Records Services of South Africa (NARSSA), for a collaborative project focused on researching and writing the histories of universities in South Africa, shed significant light on both the extremely fragmented nature of the record of education in South Africa, as well as on substantial challenges related to its accessibility. Before the historian of education can engage with the government’s record on education in South Africa, the splintered timeline of education administration must be reconstructed. Furthermore, once the historians of education then enters the NARSSA space, they are confronted with the fact that only a small fragment of this record has been described in archival finding aids. After pondering this state of affairs, this article considers the historiography of education in South Africa, examining the sources that have been used to construct narratives of the history of education, as well as how trends in this historiography could be viewed as reflecting the state of the archives. The article also offers some thoughts on the potential pitfalls and insights which await the industrious historian of education in these unaccessioned collections of the NARSSA.
Keywords: Archives; History of Education; Historiography; National Archives and Records Services of South Africa; Twentieth Century; University Histories